The influence of digital village construction on agricultural green development-based on the mediate role of industrial structure upgrading - Li, Zhaoguang; Hu, Kai; Shi, Qinying (Frontiers in Sustainable Food Systems, 2025)
IntroductionLeading the green transformation of agriculture through the digital economy is a crucial step toward high-quality agricultural growth. The role and mechanism of China's digital rural construction in promoting the green development of the whole process of agricultural production needs further analysis.MethodsBased on the panel data of prefecture-level cities in Henan Province from 2013 to 2022, we used the entropy topsis model, the fixed effect model, the Tobit regression model, the intermediate effect model, and the threshold effect model, aiming to explore the effects of digital village construction on agricultural green development and their regional differences, impacts paths and non-linear effects.ResultsThe study found the following: (1) The level of agricultural green development and the digital village construction have increased in Henan province, with the latter exhibiting a spatial clustering phenomena. (2) Digital village construction has a significant positive effect on green agricultural development, but this effect does not exist in mountainous areas. (3) The digital village construction can impact green agricultural development through the updating of agricultural structures. (4) The positive influence of digital village construction on green agricultural development is non-linear, with a single-threshold and increasing marginal effects.DiscussionThese findings provide references for other countries to use digital elements to promote green and sustainable development of agriculture. The main contribution of this study is to explore the role of agricultural industrial structure upgrading in the impact of digital rural construction on agricultural green development.